Localized Pleural Metastases of Renal Cell Carcinoma After Nephrectomy: A Case Report and Literature Review. Issue 1 (January 2016) - Yasuda, Yuichiro; Tobino, Kazunori; Ko, Yuki; Asaji, Mina; Yamaji, Yoshikazu; Tsuruno, Kosuke; Mukasa, Yosuke; Ebi, Noriyuki
Abstract : We herein report the case of a 61-year-old Japanese male with localized pleural metastases of renal cell carcinoma. The patient was admitted to our hospital because of dyspnea on exertion and left-sided pleural effusion. He had undergone right radical nephrectomy 10 years previously. Contrast-enhanced whole-body computed tomography revealed scattered nodular thickening of the left pleura with contrast enhancement and left-sided pleural effusion. Thoracoscopy performed under local anesthesia was applied to obtain a biopsy of the pleural nodules, and the specimen was consequently diagnosed as exhibiting pleural metastasis of renal cell carcinoma, clear cell type.